pH and acid phosphatase determinations after growth of Aspergillus nidulans on solid medium - W. MACCHERONI Jr.; S. R.C. POMBEIRO; N. M. MARTINEZ-ROSSI; A. ROSSI (Fungal Genetics Reports, 1991)
pH and acid phosphatase determinations after growth of Aspergillus nidulans on solid medium